Polyarteritis Nodosa Presenting as Digital Gangrene and Breast Lesion following Exposure to Silicone Breast Implants - Yamen Homsi; John Andrew Carlson; Samer Homsi (Case Reports in Rheumatology)
Polyarteritis nodosa (PAN) is a rare systemic necrotizing vasculitis of small and medium sized arteries. We report a case of a 49-year old woman who presented with PAN following exposure to silicone breast implants. Although the relationship between silicone implants and connective tissue diseases has been investigated in the literature, no prior reports were found documenting PAN after silicone mammoplasty. While the pathogenesis of idiopathic PAN is not known yet, responsiveness to immunosuppressive therapy may suggest an immunologic mechanism. More robust research is needed to understand the connection between silicone breast implants and autoimmunity.